Obliterated cavum septi pellucidi: Clinical significance and role of fetal magnetic resonance - Ilaria Fantasia; Claudia Ciardo; Gabriella Bracalente; Elisa Filippi; Flora Maria Murru; Anita Spezzacatene; Maura Bin; Olivia Mendez Quintero; Elisa Montaguti; Christoph Lees; Katherine Papanikolaou; Gianluigi Pilu; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The objective of this study was to describe a cohort of fetuses with an ultrasound prenatal diagnosis of obliterated cavum septi pellucidi (oCSP) with the aim to explore the rate of associated malformations, the progression during pregnancy and the role of fetal magnetic resonance imaging (MRI). Material and methods This was a retrospective multicenter international study of fetuses diagnosed with oCSP in the second trimester with available fetal MRI and subsequent ultrasound and/or fetal MRI follow‐up in the third trimester. Where available, postnatal data were collected to obtain information on neurodevelopment. Results We identified 45 fetuses with oCSP at 20.5 weeks (interquartile range 20.1–21.1). oCSP was apparently isolated at ultrasound in 89% (40/45) and fetal MRI found additional findings in 5% (2/40) of cases, including polymicrogyria and microencephaly. In the remaining 38 fetuses, fetal MRI found a variable amount of fluid in CSP in 74% (28/38) and no fluid in 26% (10/38). Ultrasound follow‐up at or after 30 weeks confirmed the diagnosis of oCSP in 32% (12/38) while fluid was visible in 68% (26/38). At follow‐up MRI, performed in eight pregnancies, there were periventricular cysts and delayed sulcation with persistent oCSP in one case. Among the remaining cases with normal follow‐up ultrasound and fetal MRI findings, the postnatal outcome was normal in 89% of cases (33/37) and abnormal in 11% (4/37): two with isolated speech delay, and two with neurodevelopmental delay secondary to postnatal diagnosis of Noonan syndrome at 5 years in one case and microcephaly with delayed cortical maturation at 5 months in the other. Conclusions Apparently isolated oCSP at mid‐pregnancy is a transient finding with the visualization of the fluid later in pregnancy in up to 70% of cases. At referral, associated defects can be found in around 11% of cases at ultrasound and 8% at fetal MRI indicating the need for a detailed evaluation by expert physicians when oCSP is suspected.